The indicator of entire functions with rapidly oscillating coefficients - P. V. Filevych (Математичні Студії, 2011)
Let f(z)=∑^∞_{n=0} c_n z^n be an entire function of order ρ_f∈(0,+∞) , let σ_f and h_f(θ) be the type and the indicator of the function f, respectively, let (p_n) be a sequence of positive integers with Hadamard gaps and f_t(z)=∑^∞_{n=0}e^{ip_n t} c_n z^n, where t∈R. Then, for almost every t∈R , the equality h_{f_t}(θ)=σ_f holds for every θ∈R.